Coronary artery fenestration as rescue management of intramural haematoma with luminal compression. Issue 1 (6th March 2019) - Bresson, Didier; Calcaianu, Mihaela; Lawson, Bree; Jacquemin, Laurent
Abstract: Conservative management is the first‐line treatment for spontaneous coronary artery dissection (SCAD) with stable haemodynamic status and thrombolysis in myocardial infarction three flow on angiography. However, in a few very specific patients, recurrent ischemia, or haemodynamic instability necessitates revascularization. Here, we describe a case of successful optical coherence tomography (OCT)‐guided percutaneous coronary intervention (PCI) with a cutting balloon. We performed fenestration at multiple decompression sites prior to stenting in an intramural haematoma with luminal compression. Rescue management of SCAD with luminal compression is a critical issue, because SCAD is an emergent clinical condition affecting young patients with a severe prognosis. To our knowledge, there are no large published series evaluating procedural success rates and long‐term follow‐up of this technique.